Effects of spironolactone and metoprolol on QT dispersion in heart failere - Akbulut, M; Özbay, Y; Ilkay, E; Karaca, I; Arslan, N (Int Heart Journal Assoc, 2003)
The effects of spironolactone or metoprolol added to a conventional treatment protocol on QT dispersion, which is accepted as a Sudden cardiac death predictor, were evaluated in heart failure patients.? A total of 105 New York Heart Association class III patients were included in this study. The conventional treatment protocol was standardized by giving ramipril, furosemide, and digoxin to all patients for 3 weeks at the same doses. At the end of this period, the patients were divided into three groups. Conventional treatment was continued in group 1, 25 mg spironolactone was added in group 2, and 12.5 mg metoprolol was added in group 3, Patients were followed for 12 weeks and clinical and laboratory tests were conducted at 3 week intervals. No significant change in corrected QT dispersion was observed in group 1 at the end of 12 weeks (corrected QT dispersion: 80 +/- 2 msc to 79 +/- 2 msc, P: 0.22). However, corrected QT dispersion in group 2 was reduced by 32.5% (83 +/- 2 insc to 56 +/- 1 msc; P: 0.01). A 32.9% reduction in corrected QT dispersion (79 2 ruse to 53 2 msc; P: 0.0 1) was observed in group 3. In conclusion, the addition of spironolactone or metoprolol to a conventional treatment in heart failure patients resulted in improved clinical conditions and the significant decrease in sudden death predictors corrected QT dispersion. The effects of spironolactone and metoprolol on corrected QT dispersion were similar.
Keywords: spironolactone; metoprolol; QT dispersion; heart failure